Dual catalytic function of 1,3-dialkylimidzolium halide ionic liquid on the dehydration of fructose to 5-hydroxymethylfurfural - Ryu, Jihye; Choi, Jae-Wook; Suh, Dong Jin; Ahn, Dong June; Suh, Young-Woong (ELSEVIER, 2012)
In the fructose dehydration to 5-hydroxymethylfurfural (HMF) in dimethyl sulfoxide, the catalytic function of 1,3-dialkylimidazolium-based ionic liquids with different counter-anions was investigated. It was found that the effects of alkyl chain length and additional alkyl group in Cl-containing ionic liquids were negligible whereas the activity of 1-butyl-3-methylimidazolium-based ionic liquids was considerably changed by varying the anion (particularly, halide ions). The latter finding was confirmed by the control experiment result that the addition of KBr or Ca(CH3COO)(2) dramatically tuned the catalytic activity of 1-butyl-3-methylimidazolium chloride. From these results and the proposed reaction pathway, it was consequently believed that 1,3-dialkylimidazolium halide contained the dual catalytic function to act as both Bronsted acid and nucleophile for the fructose dehydration to HMF. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: DIMETHYL-SULFOXIDE; BIOMASS; CONVERSION; FUELS; MECHANISM; SOLVENT